Prospects of Using of κ-Opioid Receptor Agonists U-50,488 and ICI 199,441 for Improving Heart Resistance to Ischemia/Reperfusion; Bulletin of Experimental Biology and Medicine; Vol. 159, iss. 6 - Tsibulnikov S. Yu. Sergey Yurjevich; Maslov L. N. Leonid Nikolaevich; Mukhomedzyanov A. V. Aleksandr Valerjevich; Krylatov A. V. Andrey Vladimirovich; Tsibulnikova M. R. Margarita Radievna; Lishmanov Yu. B. Yury Borisovich (2015, 2015)
Title screen